Study of reticulated vitreous carbon surface treated by plasma immersion ion implantation for electrodes production - Silva, L. L. G.; Conceicao, D. A. S. [UNESP]; Oishi, S. S. [UNESP]; Toth, A.; Ueda, M.; VanDeSanden, MCM; Dimitrova, M.; Ghelev, C. (Iop Publishing Ltd, 2012)
RVC samples were treated by nitrogen plasma immersion ion implantation (N-PIII) for electrodes production. High-voltage pulses with amplitudes of -3.0 kV or - 10.0 kV were applied to the RVC samples while the treatment time was 10, 20 and 30 min. The samples were characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electrochemical measurements. The SEM images present an apparent enhancement of the surface roughness after the treatment probably due to the surface sputtering during the PIII process. This observation is in agreement with the specific electrochemical surface area (SESA) of RVC electrodes. An increase was observed of the SESA values for the PIII-treated samples compared to the untreated specimen. Some oxygen and nitrogen containing groups were introduced on the RVC surface after the PIII treatment. Both plasma-induced process: the surface roughening and the introduction of the polar species on the RVC surface are beneficial for the RVC electrodes application.